Penerapan Sistem Informasi Manajemen Pendidikan dalam Proses Pembelajaran dan Strategi Penilaian Kinerja dalam Pendidikan - Chintya Pradilla Putri; Muhammad Irwan Padli Nasution; Sri Suci Ayu Sundari (MAMEN: Jurnal Manajemen, 2023)
In the application of educational management information systems in the learning process and work assessment strategies, it can also be principled by the effective and efficient use of information technology, information technology is also one of the learning media that is widely used in various fields of education because it increases effectiveness and efficiency in the learning process. This study aims to find out how management information systems are used in Indonesian learning and education. The method used in this study is the method of observation, and documentation for data collection. Data collection, data reduction, data presentation, and drawing conclusions or verification consist of data analysis stages. The results of this study indicate that by utilizing educational data processing applications called Principal Data (Dapodik) and information technology to support the learning process in providing educational services by facilitating practical learning by using or utilizing technological infrastructure called computers, shows the conclusion that the application of information systems management is very important especially in the field of learning and educational institutions.